Improving Teacher Performance Through Discipline, Transformational Leadership, Work Motivation, and Organizational Culture (Empirical Study Using Path Analysis on Public Elementary School Teachers in East Jakarta) - Sjafty Nursitti Maili; Sri Setyaningsih; Herfina Herfina (Journal of World Science, 2025)
Teacher performance is a key factor in achieving quality education because teachers not only serve as instructors but also as educators, role models, and agents of change in shaping the character and competencies of students. However, optimizing teacher performance still faces challenges related to discipline, leadership, organizational culture, and work motivation. This study aims to find strategies to improve teacher performance through these factors. The research method uses a quantitative approach with path analysis and SITOREM. The research population involved 513 public elementary school teachers in Region 2 of East Jakarta with a sample of 225 teachers. The results showed that discipline (?=0.424; p=0.001), transformational leadership (?=0.134; p=0.005), organizational culture (?=0.088; p=0.001), and work motivation (?=0.087; p=0.002) have a direct and significant effect on teacher performance. In addition, discipline (?=0.110; p=0.002), transformational leadership (?=0.225; p=0.001), and organizational culture (?=0.290; p=0.001) also have a significant effect on work motivation. However, work motivation does not function effectively as an intervening variable in the indirect influence of these three factors on teacher performance. The implications of these findings emphasize the importance of strengthening discipline, transformational leadership, and organizational culture directly to improve teacher performance. More effective development strategies should focus on these factors, while work motivation plays a supporting role rather than a primary mediating role.